The Impact of Gut Microbiota on Parkinson's and Alzheimer's Diseases: A Review of Medical Literature. - Joanna Jakubiec; Julita Gmitrzuk; Zuzanna Malinka; Katarzyna Wiśniewska; Anna Jachymek; Martyna Opatowska; Tomasz Kucharski; Marta Piotrowska (Nicolaus Copernicus University in Toruń, 2024)
Introduction Neurodegenerative diseases, such as Parkinson's disease (PD) and Alzheimer's disease (AD), pose a major public health challenge due to their progressive nature and profound impact on patients and healthcare systems. Emerging evidence underscores the key role of the gut microbiota in the pathogenesis and progression of these diseases. This paper examines the current state of knowledge on the impact of the gut microbiota on PD and AD, focusing on mechanisms such as modulation of inflammation, blood-brain barrier integrity, neurotransmitter production and amyloid pathology. Future research should target the potential hidden in the gut to fully exploit the therapeutic potential of the gut microbiota in neurodegenerative diseases. Aim of the study This review aims to summarize the current state of knowledge on the impact of the gut microbiota on neurodegenerative diseases, mainly Parkinson's and Alzheimer's disease. Materials and methods The PubMed database and articles from the last 10 years were reviewed. Keywords used in the search included "gut microbiota," "Parkinson's disease," "Alzheimer's disease," and "gut-brain axis." Selected studies were then analyzed to obtain information on the mechanisms of action. Conclusions Intestinal microflora plays a significant role in the pathogenesis of Parkinson's and Alzheimer's diseases. Modulating it through dietary interventions, probiotics and prebiotics holds promise for new therapeutic strategies. Research on the gut-brain axis and its impact on neurodegeneration will enable the creation of new therapies.